Gut Microbiota and Human Health: The Nutrition Connection-A Systematic Review - Gladys Jepkemoi; Wesley Bor; Catherine Gichunge (Kabarak Journal of Research & Innovation, 2026)
A well-balanced intestinal microbial ecosystem is fundamental to human health, influencing digestion, metabolism, immunity, and neurological processes. Growing evidence demonstrates that diet plays a central role in shaping microbial composition and functionality. This systematic review examined the influence of dietary patterns on the human gut microbiota and their consequent effects on health. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Thirty studies were screened for eligibility, of which thirteen met the inclusion criteria. Relevant literature was sourced from PubMed, Google Scholar, Science Direct, and African Journals Online. Data were extracted on dietary interventions and patterns that modulate gut microbiota composition and function, with key outcomes including microbial diversity, metabolic resilience, inflammation, and long-term health effects associated with diet-induced microbial changes. Findings from randomized controlled trials indicate that fiber-rich, Mediterranean, and plant-based diets promote microbial diversity, enhance metabolic resilience, and reduce inflammation. Observational studies further suggest long-term associations between these dietary patterns and reduced risks of metabolic disorders, gastrointestinal diseases, and adverse mental health outcomes. In contrast, diets high in fat, sugar, and processed foods were consistently linked to dysbiosis and increased disease risk. However, uncertainties remain regarding the long-term efficacy of probiotic supplementation and the impact of artificial food additives on microbial integrity. Future research should prioritize mechanistic studies on diet-induced microbial changes and the development of targeted dietary guidelines informed by microbiome profiling. Additionally, long-term clinical trials are needed to validate personalized nutrition and microbiome-based interventions for sustainable gut health.